Demands and resources of the work-family interface among micro-entrepreneurs in Chile - Lorena Armijo; Antonia Lara; Gabriela Sepúlveda O. (Administrative Sciences, 2022)
This research was designed to test how the demands-resources model is associated with the work-family interface. The present paper focused on time pressure and workload measured according to self-efficacy and personal autonomy as well as the perceptions of satisfaction with that balance. We developed an interpretative qualitative study of the meaning of the work-family interface by concentrating on the paradoxes that emerge from this relationship and from the bidirectionality. A qualitative methodology was used, and data were obtained through 44 semi-structured interviews with male and female micro-entrepreneurs from Chile who were selected according to inclusion criteria such as sex and type of micro-entrepreneur as well as their work-family balance. The interviewees had different family configurations. The results show that the group developed dual perceptions of the interface, with workload and time pressure becoming resources, and these aspects could be managed in their favor to reinforce the development of other personal resources such as autonomy and self-efficacy. The interviewees also made analytical adjustments to context sequences so that demands could be resolved subjectively by turning them into resources that provide meaning to the actions and give legitimacy to their personal decisions. The study contributes to the literature by providing a better understanding of the perceptions of micro-entrepreneurs regarding the positive connections between family and work and the negative consequences of the conflict to redefine the demands-resources model.
Keywords: 350; demands-resources model; micro-entrepreneurship; work-family interface